Small Characters, Big Worlds, and Intertextual Reading - Margaret Mackey (Strenae)
Shirley Hughes published six picturebooks about siblings Lucy and Tom between 1960 and 1987. The set of connected titles fulfills a major condition of being a series: the stories are related and feature the same characters. But the books do not follow the kind of set pattern of seriality that we normally expect: they do not follow each other in a predictable sequence, nor do they abandon sequence for reiteration and repetition of an unchanging story time. This article investigates how these books relate to each other in terms of occupying a “big world” that overflows the boundaries of a single title. It explores their condition of existing “beside” each other instead of before or after and instead of simple reiteration. Finally, it examines what these books offer to the novice interpreters who engage with them.